Evaluation of Organization Structure as Component of Quality Improvement for Maternal and Child Health Promotion in Baghdad City’s Primary Health Care Centers - Saadoon, naji; Khalifa, mohammed (Iraqi National Journal of Nursing Specialties, 2014)
A descriptive evaluation study is conducted on primary health care centers in Baghdad City in order to evaluate the organization structure as component of quality improvement of maternal and child health promotion from April 10th 2012 to May20th 2013. A total of (22) primary health care centers. Study instrument was comprised of three questionnaires and overall items included in these questionnaire were (65) items. Data are collected through the utilization of the developed questionnaire and the interview technique as means of data collection. Data are analyzed through the application of descriptive statistical data analysis methods which includes the measurement of the frequencies, percentages, and computation of mean scores, and inferential statistical data analysis approach which includes the measurement of the multiple linear regressions and factor analysis. The study findings reveal that the organizational structure has experienced severe lack of fund, lectures, availability of library, availability of classroom, availability of whiteboard, and use of internet to communicate with consumers. Furthermore, some organizational structure moderately experience lack of air-conditioned units, availability of computers, availability of data show, planning to establish or expand the health promotion hall and the number of the staff in the health promotion unit. On the other hand, the remaining items of the organizational structure have experienced better status than other items, and the aspect of staff has revealed that most of them staff has lacked practices and experiences relative to their task as providers of health promotion service to pregnant women as consumers. The study recommend that great efforts can be presented by the Ministry of Health for the improvement of the organizational structure for the sake of better continuous quality improvement of maternal and child health promotion, consumers can be considered vital participants who should be provided with benefit-wise educational courses by which their health promotion can be motivated and developed, staff has to be presented with better education and opportunities for well-structured training courses in the area of health promotion, and further studies can be conducted on large sample size and nation-wide oriented ones.